The politics of popular culture : negotiating power, identity, and place - Nieguth, Tim (McGill-Queen's University Press, 2015)
Examines the relationship between popular culture and politics. This book stresses that popular culture is politically important because it reflects and operates within broader socio-political conditions, can transport political ideas and ideologies, and is a site where identities and institutions are shaped, contested, and reproduced.